Ecological Wisdom Research Trends Over Decade in Landscape Planning: A Systematic Review - Rosyi Damayanti Manningtyas; Katsunori Furuya (http://arl.faperta.ipb.ac.id/, 2023)
Ecological wisdom has become an emerging field in the context of landscape planning and design practices for achieving sustainability and resilience. Several scholars have published empirical research papers in this field, and some have also conducted reviews to explore its concept and framework. However, since the empirical research varies, no study has made a systematic literature review and thus encountered difficulties in determining the research topic and problem. Moreover, the research approach and data analysis method could differ based on study site characteristics. Therefore, this study aims to identify and analyze the research topic and problem discussed, site characteristics, and methodology of ecological wisdom studies from 2012 to 2021 by conducting systematic literature reviews involving descriptive analysis, and thematic analysis. The analysis of selected primary studies revealed that recent ecological wisdom studies focus on four topics: exploration, in-depth concept, method introduction, and evidence-based study. Most of the problems discussed in primary studies have focused on acquiring and applying ecological wisdom in practice for contemporary planning and design related to landscape sustainability and resiliency. The characteristics of the study sites were grouped into four categories: sites with unique landscape features, historical or preserved sites, sites with environmental problems or limitations, and sites with high biodiversity. The research methodology developed in ecological wisdom studies uses one or a combination of qualitative, quantitative, and/or spatial approaches involving field measurements and spatial modelling. Finally, the contribution, limitation, and opportunities for future improvements.